2019
DOI: 10.1111/jcmm.14633
|View full text |Cite
|
Sign up to set email alerts
|

TGFBIp mediates lymphatic sprouting in corneal lymphangiogenesis

Abstract: Corneal lymphangiogenesis plays a key role in diverse pathological conditions of the eye. Here, we demonstrate that a versatile extracellular matrix protein, transforming growth factor‐β induced protein (TGFBIp), promotes lymphatic sprouting in corneal lymphangiogenesis. TGFBIp is highly up‐regulated in inflamed mouse corneas. Immunolocalization of TGFBIp is detected in infiltrating macrophages in inflamed mouse corneas. Subconjunctival injection of liposomal clodronate can significantly reduce macrophage infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…53 Furthermore, a recent study showed that phosphorylation of FAK was enhanced by TGFBIp and was suppressed significantly by an integrin α5β1 inhibitor. 54 Considering that TGFBIp interacts with several integrins 55 including α5β1, 56 these data indicate that TGFBIp is an upstream regulator of the integrin/FAK/PGC-1α signalling pathway. Accordingly, TFEB in GCD2 corneal fibroblasts can be reduced by reduced integrin/FAK/PGC-1α signalling.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…53 Furthermore, a recent study showed that phosphorylation of FAK was enhanced by TGFBIp and was suppressed significantly by an integrin α5β1 inhibitor. 54 Considering that TGFBIp interacts with several integrins 55 including α5β1, 56 these data indicate that TGFBIp is an upstream regulator of the integrin/FAK/PGC-1α signalling pathway. Accordingly, TFEB in GCD2 corneal fibroblasts can be reduced by reduced integrin/FAK/PGC-1α signalling.…”
Section: Discussionmentioning
confidence: 92%
“…Although it remains unclear whether the pathogenic mutation causes a loss‐of‐function or gain‐of‐function of TGFBIp, Maeng et al showed that TGFBIp activates focal adhesion kinase (FAK) signalling 53 . Furthermore, a recent study showed that phosphorylation of FAK was enhanced by TGFBIp and was suppressed significantly by an integrin α5β1 inhibitor 54 . Considering that TGFBIp interacts with several integrins 55 including α5β1, 56 these data indicate that TGFBIp is an upstream regulator of the integrin/FAK/PGC‐1α signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β has also reportedly regulated lymphatic vessel sprouting during development [ 44 , 45 ]. In the cornea, TGF-β-induced protein (TGFBIp), which is abundant in the cornea, enhances lymphangiogenesis; however, the underlying mechanisms remain unknown [ 46 ].…”
Section: Cytokines and Molecular Markers For Lymphangiogenesismentioning
confidence: 99%
“…However, specific cytokine-induced lymphangiogenesis is context-dependent. For example, TGF-β can induce or inhibit lymphangiogenesis [ 44 , 46 ].…”
Section: Cytokines Promote or Inhibit Lymphangiogenesis In Various Disease Modelsmentioning
confidence: 99%
“…In vitro, the TGFBIp’s effect is mediated by the pathway of integrin α 5 β 1 -FAK. Integrin α 5 β 1 blockade can significantly inhibit lymphatic sprouting induced by TGFBIp [ 43 ].…”
Section: Integrins and The Eyementioning
confidence: 99%